(untitled) - Torres-Coronas, Teresa (Hersley, PA, 2005)
This book provides a deep discussion about e-HRM issues so the reader can have a thoughtful background about the key role played by those who participate in e-HRM activities. A variety of experiences are provided to involve the reader in real problems and to help the reader gain an understanding of current and future e-HRM challenges. E-Human Resources Management: Managing Knowledge People also explores the impact of IT on communication effectiveness, the concept of protean career, the integration of handheld computer technology into HR practice, the B2E models, and perspectives in organizational development and IT.
Keywords: Knowledge management,Perrsonnel management,Information technology; Management